Jawa, Islam dan Nusantara - Riwanto Tirto Sudarmo (ISLAM NUSANTARA:Journal for the Study of Islamic History and Culture, 2021)
The two books being reviewed are compilation of papers on the belief system and religion that are practiced by diverse local communities in the Indonesian archipelago. The first book concerned with the experience of repression and political persecution by the many local communities after the 1965 event, while the second book describe the adaptation processes of those local communities to islamization which is assumed as completed. Academically, the books is successful in exposing the transformation of religious life of diverse local communities located in different places in Indonesia.